2006
DOI: 10.1021/jm051256o
|View full text |Cite
|
Sign up to set email alerts
|

Extra Precision Glide:  Docking and Scoring Incorporating a Model of Hydrophobic Enclosure for Protein−Ligand Complexes

Abstract: A novel scoring function to estimate protein-ligand binding affinities has been developed and implemented as the Glide 4.0 XP scoring function and docking protocol. In addition to unique water desolvation energy terms, protein-ligand structural motifs leading to enhanced binding affinity are included: (1) hydrophobic enclosure where groups of lipophilic ligand atoms are enclosed on opposite faces by lipophilic protein atoms, (2) neutral-neutral single or correlated hydrogen bonds in a hydrophobically enclosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
4,408
0
19

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 5,619 publications
(4,455 citation statements)
references
References 40 publications
28
4,408
0
19
Order By: Relevance
“…This so-called hydrophobic enclosure of the adenine binding site enhances the hydrogen bonding interactions to the hinge region. 28 Residues 181 and 974, which form the top and bottom of the adenine binding site, are highly conserved. The conservation is probably a result of steric constraints: Larger hydrophobic residues would prevent ATP from binding.…”
Section: Discussionmentioning
confidence: 99%
“…This so-called hydrophobic enclosure of the adenine binding site enhances the hydrogen bonding interactions to the hinge region. 28 Residues 181 and 974, which form the top and bottom of the adenine binding site, are highly conserved. The conservation is probably a result of steric constraints: Larger hydrophobic residues would prevent ATP from binding.…”
Section: Discussionmentioning
confidence: 99%
“…The extra-precision (XP) mode of GLIDE was used to achieve an accurate pose prediction. The GLIDE XP mode utilizes an improved scoring function, including a water desolvation energy term and protein-ligand structural motifs that result in enhanced binding affinity [18] . For docking, the receptor structures were preprocessed using protein refinement 1131 www.chinaphar.com Lee BH et al Acta Pharmacologica Sinica npg components in the GLIDE docking package.…”
Section: Pulse Protocols and Analysismentioning
confidence: 99%
“…The pharmacophore models were generated from the ligand co-crystallized complex structures of these targets using the LigandScout program [12] , and each PBVS was performed using the program Catalyst [13,14] . To avoid the target dependency of docking programs, three docking programs, namely DOCK [15,16] , GOLD [17][18][19][20] , and Glide [21,22] , were used in the DBVS. The results for eight tested targets indicated that the pharmacophore-based method generally outperforms all three docking methods in retrieving actives from databases.…”
mentioning
confidence: 99%